Program-Based Teaching and Learning To Increase Competency in Undergraduate Medical Students Using a Model of the Revised National Tuberculosis Control Program - Vincent Mangayarkarasi (American Society for Microbiology, 2019)
Teaching methods need continuous innovation to encourage undergraduate medical students to enhance their competency level and skills. Every undergraduate medical student should be able to discuss the Revised National Tuberculosis Control Program (RNTCP) and Direct Observed Treatment Short (DOTS) course recommended by the World Health Organization (WHO). The DOTS strategy was launched in 1992, with the objective of detecting at least 70% of new sputum-positive tuberculosis (TB) patients and curing at least 85% of such patients. The aim of this study was to improve the competency level of Undergraduate (UG) Bachelor of Medicine and Bachelor of Surgery (MBBS) students by teaching them the objectives of the RNTCP at a program implementation site in the medical college. The RNTCP could be considered and conducted as Program-Based Teaching and Learning (PBTL) for the UG medical students. The following skills were to be implemented in the RNTCP PBTL: Sputum Collection, Ziehl-Neelsen staining and Grading, Mantoux test, and TB Culture and Molecular test (Gene Xpert). Phase II undergraduate MBBS students (N = 104) participated in the PBTL. This study was conducted in the RNTCP laboratory of a tertiary-care teaching medical college hospital. This descriptive study included advanced skill-based teaching such as Directly Observed Practical Skill, Demonstration-Observation-Assistance-Performance, Video Demonstrations, Role Play, and Group interaction as teaching tools. Pre-/post-test, Objective Structured Practical Examination, and frequently asked questions were used as assessment tools. The pre- and post-test marks were compared, and other assessments were also analyzed using SPSS. At the end of the teaching program, the feedback forms were collected from students and analyzed. The mean score obtained for 104 MBBS students in the pre-test, post-test, and other assessment tools were 213.3 and 487.5, respectively (p < 0.001). We conclude that skill-based teaching and learning tools to teach public health program like RNTCP provide valuable essential skills for undergraduate medical students. This Program Based Teaching and Learning could be successfully extended to all medical colleges.